Effect of semi-solid Processing on Microstructure and Tribological Characteristics of Al-10Cu alloy - L., Sankara Rao (IIT(BHU), Varanasi, 2018)
Abstract is available in the attachment
This Thesis submitted by PhD. Scholar IIT(BHU), Varanasi. & Supervised by Prof. S. N. Ojha and Prof. A. K. Jha.
Keywords: Effect of Semi-Solid; Microstructure; Tribological